Hemorrhage into the brain abscess cavity with Fallot's tetralogy - Kaplan, M; Topsakal, C; Cihangiroglu, M (Karger, 2006)
Hemorrhage into the abscess cavity is a complication of brain abscess. It has been reported to be due to inflammation which results in the damage of the fragile neovasculature of the abscess wall. Hypoxia caused by Fallot's tetralogy or other congenital heart diseases facilitates the damage of these vessels with the lacking supportive tissues, and in turn intracavital bleeding. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: brain abscess; Fallot's tetralogy; hemorrhage